AN ANALYTICAL STUDY OF THE URBAN GREEN SPACES SURROUNDING THE ROYAL CEMETERY - AL-Rahman, Sundus; Qassim, S.; Jisim, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The spaces surrounding the royal cemetery were chosen for the purposes of the practical study as they are an important historical, cultural, and urban landmark not only for the Adhamiya district, but at the level of Baghdad governorate. The research aimed to increase environmental awareness and strategic planning among the designers of urban green spaces and decision-makers in the design and implementation of these spaces to increase their efficiency and functionality. The research followed the comparative-descriptive-analytical approach to extract data for these spaces, which went through two phases before development in 2020 and after development in 2021 in the light of five tools for collecting and analyzing information: field survey, climatic factors analysis, urban fabric analysis, personal interviews, and a questionnaire.The results of the study also confirmed the importance of afforestation in reducing temperatures for the micro-climate of spaces, increasing relative humidity, reducing wind speed, and changing its direction.